Dielectric and infrared inference of thermo-oxidative aging of a bismaleimide composite material. (15th September 2016) - Daily, Connor; Barnard, Dan J.; Jones, Roger W.; McClelland, John F.; Bowler, Nicola
Abstract: The degradation of a thermally-aged bismaleimide-glass fiber composite system was assessed via spectroscopic methods. Composite samples were subjected to accelerated isothermal aging at temperatures (275, 300, 325, 350 and 375  ° C) near or above the suggested upper usage limit of 290 °C. Broadband dielectric spectroscopy was used to measure changes in the dielectric spectra of aged composites from 1 kHz to 2 MHz, while chemical changes in the resin were identified with Fourier transform infrared photoacoustic spectroscopy. Additionally, samples were mechanically assessed via a double-notch compression test. Relationships between the dielectric, photoacoustic, and mechanical properties were inferred from the results.